Randomized controlled trial of cognitive behaviour therapy for comorbid post‐traumatic stress disorder and alcohol use disorders. (4th April 2013) - Sannibale, Claudia; Teesson, Maree; Creamer, Mark; Sitharthan, Thiagarajan; Bryant, Richard A.; Sutherland, Kylie; Taylor, Kirsten; Bostock‐Matusko, Delphine; Visser, Alicia; Peek‐O'Leary, Marie
Abstract Aims This study aimed to test the efficacy of integrated cognitive behaviour therapy (CBT) for coexisting post‐traumatic stress disorder (PTSD) and alcohol use disorders (AUD). Setting Clinics across Sydney, Australia. Design Randomized controlled trial of 12 once‐weekly individual sessions of either integrated CBT for PTSD and AUD (integrated therapy, IT; n = 33) or CBT for AUD plus supportive counselling (alcohol‐support, AS; n = 29). Blind assessments were conducted at baseline and post‐treatment and at 5 [standard deviation (SD) = 2.25] and 9.16 (SD = 3.45) months post‐treatment. Participants Sixty‐two adults with concurrent PTSD and AUD. Measurements Outcomes included changes in alcohol consumption (time‐line follow‐back), PTSD severity [clinician‐administered PTSD scale (CAPS)], alcohol dependence and problems, and depression and anxiety. Findings Reductions in PTSD severity were evident in both groups. IT participants who had received one or more sessions of exposure therapy exhibited a twofold greater rate of clinically significant change in CAPS severity at follow‐up than AS participants [IT 60%, AS 39%, odds ratio (OR): 2.31, 95% confidence interval (CI): 1.06, 5.01]. AS participants exhibited larger reductions than IT participants in alcohol consumption, dependence and problems within the context of greater treatment from other services during follow‐up. Results lend support to a mutually maintaining effect between AUD and PTSD. Conclusions Individuals with severe and complex presentations of coexisting post‐traumatic stress disorder (PTSD) and alcohol use disorders (AUD) can derive substantial benefit from cognitive behaviour therapy targeting AUD, with greater benefits associated with exposure for PTSD. Among individuals with dual disorders, these therapies can generate significant, well‐maintained treatment effects on PTSD, AUD and psychopathology.